Balloon-Occluded Retrograde Transvenous Obliteration of a GastroRenal Shunt using Hydrogel-Coated Coil Embolization - Ginat, Daniel T. (Radiol Case Rep, 2015)
Balloon-retrograde transvenous obliteration (BRTO) can be an appropriate treatment modality for hepatic encephalopathy in the setting of portal-systemic shunting in selected patients. We describe a case of a large gastro-renal shunt that was successfully treated via combined BRTO and expandable hydrogel-coated coil embolization, with an emphasis on technique.